Peran Konseling Multikultural dalam Mengatasi Stigma Gangguan Kesehatan Mental - Seprianto Seprianto; Sovatunisa Soleha; Dina Hajja Ristianti; Hendra Harmi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
ABSTRACT: Counseling is a process that assists individuals in overcoming barriers and difficulties that hinder their personal growth and development of their maximum potential. Through multicultural counseling, counselors can provide accurate education about mental health disorders to individuals and the community in Jambu Rejo village. This can help eliminate negative stereotypes and misunderstandings that may exist about mental health disorders. Based on previous research findings, multicultural counseling plays a significant role in helping individuals overcome stigma and increasing understanding of mental health. The research method employed in this study is qualitative research, collecting data through in-depth interviews with multicultural counselors practicing in Jambu Rejo village. The data obtained will be analyzed using a thematic approach to identify relevant themes related to the role of multicultural counseling in overcoming stigma. The results of this study indicate that multicultural counseling is crucial. Multicultural counselors can help individuals overcome stigma through a culturally sensitive approach, accurate information provision, development of social support, increased self-awareness, and advocacy for stigma eradication. Thus, multicultural counselors have a significant role in assisting individuals in overcoming stigma, providing effective counseling services, and enhancing the mental and social well-being of the community in Jambu Rejo village. KEYWORDS: Multicultural Counseling, Stigma, Mental Health Disorders, Jambu Rejo village.